The performance of value and momentum investing strategies on the JSE, South Africa. - Ramdhani, Aviraag Nareenchand (My University, 2014)
ABSTRACT Previously, value and momentum investing strategies were widely used investment strategies by investment managers around the world. However, due to the global economic crisis that occurred in 2008, investors became uncertain regarding which investment strategy to utilise to generate the greatest amount of return. This study uses share price data of all the shares listed on the JSE over a period of 15 years to determine whether value and momentum investing generates excess returns. Furthermore, the study seeks to determine which investment strategy (value or momentum) delivers the greatest returns during bull and bear market conditions. It was found that both value and momentum investing generate excess returns and that momentum investing significantly outperforms value investing during bull and bear market conditions.
MBA 2014
Keywords: Johannesburg Stock Exchange,Investment analysis.